Structural characterization of functionalized gold nanoparticles for drug delivery in cancer therapy: a NMR based approach. Issue 29 (7th August 2015) - Coelho, Sílvia C.; Rangel, Maria; Pereira, Maria C.; Coelho, Manuel A. N.; Ivanova, Galya
<x xml:space="preserve">Abstract</x> Structure of Bortezomib loaded, surface functionalized Au nanoparticles.